FORMATION OF BASIC ORAL SPEECH SKILLS IN ENGLISH (ON THE EXAMPLE OF 8-9 CLASSES OF SECONDARY SCHOOL) (Conference Zone, 2022)
a modern school should prepare a person who is thinking and feeling, who not only has knowledge, but also knows how to use this knowledge in life, knows how to communicate and has an inner culture. The goal is not that the student knows as much as possible, but knows how to act in any situation and solve problems. This knowledge of speech is a necessary condition for the formation of a socially active person. It is necessary for everyone to speak clearly and grammatically correctly, to express his thoughts in a well-thought-out voice, free creative interpretation in oral and written form, to express emotions by various intonation means, to develop the ability to observe and communicate the culture of speech. Therefore, one of the important tasks at the present stage of teaching students is to develop speaking activities. In this article, information (on the example of 8-9 classes of Secondary School) on the formation of basic oral skills in English is obtained and opinions and comments are made.